Series of configurational movements : User activities in technology generalization - Hyysalo, Sampsa; Juntunen, Jouni K. (Elsevier, 2023)
The detailed studies of adoption and user activities indicate that continuous alterations accompany the proliferation of new technology, yet diffusion theory and system change-oriented frameworks portray the spread of technologies across a social or sociotechnical system with relatively few changes. To better reconcile the two orientations, we introduce a series of configurational movements (SCM) as a conceptual register for the generalization of new technology in society. We elaborate on the SCM with an over-a-decade-long investigation into heat pumps in Finland, one of the globally furthest progressed energy transitions. The process has thus far involved nine configurational movements, each featuring a change in the character of the technology, the ecology of actors relevant to it, and the contexts in which the technology spreads. SCM analysis further surfaces eight user activity types that have shaped how the technology, its deployment, and its markets have evolved: Adoption and routine use, adaption and adjustment, championing, user innovation, community building, peer intermediation, market creation and production of legitimating discourse on heat pumps. In all, the generalization features significant shifts in user practices, the technology, and societal impact throughout the process, not only during its early phases, instilling energy system wide change.
Keywords: Technology diffusion; Generalization process; Configurational movement; Heat pump; Energy transition; fi=Tuotantotalous|en=Industrial Management|